(untitled) (Research, Society and Development, 2020)
Burnout Syndrome (SB) is the prolonged response to chronic stress at work. It appears that health professionals are susceptible to developing such a syndrome, as they deal with intense emotions, excessive workloads and stressful situations on a daily basis, so our objective is to describe the occurrence of BS in health professionals, since such involvement comes showing itself more and more growing. The methodology applied was the literature review for the period 2011–2019, using the Medline, LILACS, SciELO and VHL databases. The descriptors were obtained through DeCs, being: "professional burnout", "consequences", "health personnel", in Portuguese, English, totaling 19 articles. As inclusion criteria, articles that used BS in health professionals in Brazil, prevalence, causes were used. Studies in which health professionals had other psychological disorders were excluded if the outcome did not occur in Brazil. As a result, 19 articles from the years 2011 to 2019 were obtained with a sample of 3,161 participants from various regions of Brazil. The prevalences found ranged from 2.7% to 58.3% among health professionals. Therefore, Burnout is a public health problem with an increasing prevalence among health professionals, therefore studies are needed to understand this syndrome to prevent new cases and treat existing ones.